C–H Functionalization of Quinoxalines - Laru, Sudip; Ghosh, Sumit; Hajra, Alakananda (Synlett, 2025)
As a powerful tool in modern organic synthesis, C–H functionalization offers an elegant shortcut to molecular complexity, enabling direct bond transformations without any pre-functionalization. In this connection, the C–H functionalization of quinoxalines offers a direct and efficient approach to modify the quinoxaline scaffold, a key structural motif in biologically active compounds and materials. This personal account describes the methodologies developed by our group for the C–H activation and functionalization of quinoxaline compounds.1 Introduction2 Difluoroalkylamidation3 ortho C–H Alkylation4 ortho C–H Amination5 Conclusion
Keywords: C–H functionalization; quinoxalines; ortho C–H functionalization; visible-light-induced functionalization; organophotocatalyst